Traumatic episodes experienced during the genocide period in Rwanda influence life circumstances in young men and women 17 years later - Rugema, Lawrence (BioMed Central, 2013)
BACKGROUND: During Rwanda’s genocide period in 1994, about 800,000 people were killed. People were murdered, raped and seriously injured. This retrospective study investigated prevalence and frequency of traumatic episodes and associated psychosocial effects in young adults in Rwanda over the lifetime, during the genocide period and in the past three years. METHODS: This is a cross-sectional population-based study conducted among men and women, aged 20 to 35 years, residing in the Southern province of Rwanda. The study population, randomly selected in a multi stage procedure, included 477 females and 440 males. Data collection was performed through individual interviewing with a structured questionnaire during the period December 2011- January 2012. The Harvard Trauma Questionnaire was used to assess traumatic episodes. All data was sex-disaggregated. Differences between groups were measured by chi square and Fischer’s exact test. Associations with socio-demographic and psychosocial factors were estimated by use of odds ratios with 95% confidence intervals in bi- and multivariate analyses. RESULTS: The participants in this study were 3 to 18 years of age in 1994, the year of the genocide. Our sample size was 917 participants, 440 men and 477 women. Women were to a higher extent exposed to traumatic episodes than men during their lifetime, 83.6% (n = 399) and 73.4% (n = 323), respectively. During the genocide period, 37.5% of the men/boys and 35.4% of the women/girls reported such episodes while in the past three years (2009-2011) 25.0% of the men and 23.1% of the women did. Women were more exposed to episodes related to physical and sexual violence, while men were exposed to imprisonment, kidnapping and mass killings. Victims of such violence during the genocide period were 17 years later less educated although married (men OR 1.47; 0.98-2.19; women OR 1.54; 1.03-2.30), without children (men OR 1.59; 1.08-2.36; women OR 1.86; 1.11-3.08) and living under extremely poor circumstances. CONCLUSION: The participants in this population-based study witnessed or experienced serious traumatic episodes during the genocide, which influenced their life circumstances 17 years later. Such traumatic episodes are however still taking place. The reasons for this need further investigation.